RAAS Inhibitor Prescription and Hyperkalemia Event in Patients With Chronic Kidney Disease: A Single-Center Retrospective Study - Riccio, Eleonora; Capuano, Ivana; Buonanno, Pasquale; Andreucci, Michele; Provenzano, Michele; Amicone, Maria; Rizzo, Manuela; Pisani, Antonio (Frontiers in Cardiovascular Medicine, 2022)
Hyperkalemia is common in patients treated with renin–angiotensin–aldosterone system inhibitors (RAASi), and represents the main cause of the large gap reported between the guidelines recommendations and real-world practice in chronic kidney disease (CKD). We conducted a CKD-population-based restrospective study to determine the prevalence of CKD patients treated with RAASi, the incidence of hyperkalemia in CKD patients treated with RAASi, and the proportion of patients with RAASi medication change after experiencing incident hyperkalemia. Among 809 CKD patients analyzed, 556 (68.7%) were treated with RAASi, and RAASi prescription was greater in stages 2-4 of CKD. Hyperkalemia occurred in 9.2% of RAASi treated patients, and the adjusted rate of hyperkalemia among patients with stage 4-5 CKD was 3-fold higher compared with patients with eGFR >60 mL/min/1.73m2. RAASi treatment was discontinued in 55.3% of patients after hyperkalemia event (74.2% discontinued therapy, 3.2% received a reduced dose and 22.6% reduced number of RAASi drugs). This study shows that the incidence of hyperkalemia is frequently observed in CKD patients treated with RAASi, and rates increases with deteriorating levels of kidney function from stage 1 to 3. RAASi medication change following an episode of hyperkalemia occurred in almost half of patients who experienced hyperkalemia.